The Construction of Immunoliposomes (Review) - M. V. Dmitrieva; I. V. Yarosh; E. V. Sanarova; A. V. Lantsova; O. L. Orlova (Разработка и регистрация лекарственных средств, 2022)
Introduction. Due to the discovery of antibodies (Ab) targeting molecule with high specificity to the ligand, the "magic bullet" concept has been successfully implemented with various immunoconjugated drugs. Since 1980, Ab conjugates with liposomes, i.e., immunoliposomes (ILs), have been widely investigated to improve the specificity and efficacy of drug therapy. This review is devoted to the characteristic of the basic structural units of ILs on the basis of data analysis of original and review articles on the topic from PubMed, ResearchGate and CyberLeninck databases.Text. ILs are liposomes to which Ab, their fragments or other ligands are usually attached by a special linker. ILs are used to deliver antitumor, cardiovascular, antiviral, antiprotozoal drugs, genetic material, imaging molecules, etc. ILs can be derived from various phospholipids of both natural and synthetic origin, charged or neutral. The most widely used phospholipids in immunoliposomal construction are phosphatidylcholines. To increase the mechanical stability of the bilayer, sterols are introduced into the lipid composition. For selective liposome delivery, targeting ligands must be attached to the nanocarrier via the spacer arm of the PEG. Several types of end-group functionalized lipopolymers are used for this purpose, usually of the general formula X-PEG-LI, where X represents a fragment containing a reactive functional group − maleimide, biotin, cyanur, amine, etc. These lipid PEG-conjugates exhibit excellent amphiphilic properties and offer excellent advantages for the modification, formulation, and delivery of various drugs. The Ab used should enhance the accumulation of the liposomal drug in the target areas with minimal cross-reactivity with healthy tissues. Ready-made drugs based on monoclonal Ab, such as trastuzumab, cetuximab, panitumumumab, bevacizumab; commercial Ab intended for research purposes, and laboratory synthesized Ab and their fragments are used in the preparation of ILs. Ab can be attached to liposomes by two main methods: direct covalent conjugation and postinsertion.Conclusion. The results of this study allowed us to summarize the variety of literature data on the composition of ILs and the possibility of using auxiliary components to achieve the goal in the development of the drug.